2019
DOI: 10.1155/2019/2756516
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Profiling by Illumina Sequencing via Template-Dependent Multiple Displacement Amplification

Abstract: Circular RNAs (circRNAs) are newly discovered incipient non-coding RNAs with potential roles in disease progression in living organisms. Significant reports, since their inception, highlight the abundance and putative functional roles of circRNAs in every organism checked for, like O. sativa, Arabidopsis, human, and mouse. CircRNA expression is generally less than their linear mRNA counterparts which fairly explains the competitive edge of canonical splicing over non-canonical splicing. However, existing metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 51 publications
(65 reference statements)
1
41
0
1
Order By: Relevance
“…Similarly, the expression of circMBNL1 was reported in human and Drosophila heads (Ashwal-Fluss et al, 2014). More than 700 common exonic circRNAs, shared between O. sativa and A. thaliana (Ye et al, 2015), were reported, and a similar observation was also observed between O. sativa Indica and other plants (Guria et al, 2019). These examples depict the conservation of circRNA that originated from the genomic locus, which evolved with a paralogous or orthologous nature.…”
Section: Conserved Naturementioning
confidence: 53%
See 4 more Smart Citations
“…Similarly, the expression of circMBNL1 was reported in human and Drosophila heads (Ashwal-Fluss et al, 2014). More than 700 common exonic circRNAs, shared between O. sativa and A. thaliana (Ye et al, 2015), were reported, and a similar observation was also observed between O. sativa Indica and other plants (Guria et al, 2019). These examples depict the conservation of circRNA that originated from the genomic locus, which evolved with a paralogous or orthologous nature.…”
Section: Conserved Naturementioning
confidence: 53%
“…Japonica, Oryza sativa ssp. Indica, Nicotiana benthamiana (Guria et al, 2019), and in 12 other plant species (Chu et al, 2017). However, their identification and characterization reveal that the biogenesis of circRNAs originates through the act of backsplicing and not through mis-splicing, as was reported previously.…”
Section: Historymentioning
confidence: 70%
See 3 more Smart Citations